Safe payments - Jonathan Chiu; Seyed Mohammadreza Davoodalhosseini; Janet Hua Jiang; Yu Zhu (Bank of Canada, 2020)
We use a simple model to study whether private payment systems based on bank deposits can provide the optimal level of safety. In the model, bank deposits backed by projects are subject to default risk that can be mitigated by a depositor's ex ante and ex post monitoring. Safe payment instruments issued by a narrow bank can also be used as a back-up payment system when the risky bank fails. Private adoption of safe payment instruments is generally not socially optimal when buyers do not fully internalize the externalities of their adoption decision on sellers, or when the provision of deposit insurance distorts their adoption incentives. Using this framework, we discuss the optimal subsidy policy conditional on the level of deposit insurance.
Keywords: E42; E50; G21; 330; Central bank research; Digital currencies and fintech; Financial institutions; Payment clearing and settlement systems